Workshop Media Pembelajaran Berbasis AI Berorientasi pada Kolaborasi dan Inovasi Siswa untuk Mendukung Proses Pembelajaran MGPM Guru PAI di SMAN 1 Sidoarjo - Muvid, Muhamad Basyrul (Abdurrauf Journal of Community Service, 2025)
Learning is an important activity to prepare a generation that has competence and character. The development of existing technology also has an impact on the teaching and learning styles of teachers and students, so that everyone must adapt. One form of technological development is the existence of artificial intelligence (AI) which has many benefits for the world of education, especially as a learning medium. Therefore, many activities are needed to socialize AI in learning, workshops are one form of real activities in educating and training teachers to be able to use AI in teaching and learning activities. The method of implementing this community service activity is preceded by direction, delivery of material, questions and answers and trials of AI applications, this activity was carried out at SMAN 1 Sidoarjo with participants from all PAI teachers who are members of the Subject Teachers' Deliberation throughout Sidoarjo Regency. The results of this community service are first, providing education to participants (teachers) about AI and its position in the world of education. Second, the types of AI that can be used as learning media and their implementation where teachers practice directly, especially the use of one of the AIs, namely mentimeter. Third, AI as a digital-based learning media to encourage the habit of collaboration and innovation for students. Collaboration and innovation competencies for students become a succession of learning objectives realized in the midst of super-fast changes amidst the uncertainty called the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity). Abstrak: Pembelajaran merupakan kegiatan yang penting untuk menyiapkan generasi yang mempunyai kompetensi dan karakter. Perkembangan teknologi yang ada turut memberikan dampak pada gaya mengajar dan belajar guru serta peserta didik, sehingga semuanya harus beradaptasi. Salah satu bentuk perkembangan teknologi ialah adanya kecerdasan buatan (AI) yang memiliki banyak manfaat bagi dunia pendidikan khususnya sebagai media pembelajaran. Oleh sebab itu, diperlukan banyak kegiatan untuk mensosialisasikan AI dalam pembelajaran, workshop menjadi salah satu bentuk kegiatan nyata dalam mengedukasi serta melatih guru untuk bisa menggunakan AI dalam kegiatan belajar mengajar. Metode pelaksanaan kegiatan pengabdian ini ialah didahului dengan pengarahan, penyampaian materi, tanya jawab dan uji coba aplikasi AI, kegiatan ini dilakukan di SMAN 1 Sidoarjo dengan peserta seluruh guru PAI yang tergabung dalam Musyawarah Guru Mata Pelajaran se Kabupaten Sidoarjo. Hasil pengabdian ini ialah pertama, memberikan edukasi kepada para peserta (guru) terhadap AI dan posisinya di dunia pendidikan. Kedua, macam-macam AI yang bisa digunakan sebagai media pembelajaran serta implementasinya di mana para guru praktik secara langsung khususnya penggunaan salah satu AI yaitu mentimeter. Ketiga, AI sebagai media pembelajaran berbasis digital untuk mendorong terjadinya habit kolaborasi dan inovasi bagi peserta didik. Kompetensi kolaborasi dan inovasi bagi peserta didik menjadi suksesi tujuan pembelajaran terwujud di tengah perubahan yang super cepat di tengah ketidakpastian yang disebut era VUCA (Volatility, Uncertainty, Complexity, Ambiguity). Kata Kunci: AI, Media-pembelajaran, kolaborasi, inovasi